Effect of Chemical and Hand thinning on the Fruit Biochemical Properties of ‘Khadrawi’ Date Palm (Phoenix dactylifera L.) during Fruit Development - M. Jalali; N. Moallemi; E. Khaleghi; S. Zivdar; M. Rahmati-Joneidabad (Majallah-i ̒Ulum-i Bāghbānī)
IntroductionThe date palm (Phoenix dactylifera L.) tree tolerate high temperatures, drought and salinity more than other fruit crop, that is why date palm tree is named the tree of life in the desert. Date palm (Phoenix dactiylifera) is one of the fruit tree crops that is cultivated in arid region of Middle East and North Africa having a significant role on the economy of many countries in these regions. Fruit thinning is one of the major operation for improving the quality of dates as also for other fruit trees. Quality of dates is improved by increasing fruit weight and size and regulating date palm production by reducing the magnitude of year to year production affecting the date palm. Date palm orchard operations include all operations that are repeated annually to produce date fruit. Alternate bearing is common phenomenon in date palms. The thinning is one of the main methods that often helps to solve this problem. The main purpose of thinning is to create a suitable balance and often to increase the leaf to cluster ratio. It is creating a balance between vegetative growth and flowering and reducing the possibility of aging in the alternate bearing. Fruit thinning is one of the necessary operations that affects the growth, quality, fruit yield and regulation of the alternate bearing of the tree. The thinning process is performed manually, mechanically and chemically. Therefore, choosing a thinning method that saves time and money is necessary for date palms, especially in critical situations. The purpose of this experiment was to investigate the effects of manual and chemical thinning on the qualitative characteristics of date fruit at different stages of development for the Khadrawi cultivar. Materials and MethodsAn experiment was carried out as factorial experiment based on randomized complete block design with 3 replications at Shahid Chamran University of Ahvaz in 2022 and 2023. The Experimental factors included: hand thinning (No hand thinning, removal of 33%, removal of 25% of the total number of strands) and chemical thinning (zero, 50 and 100 mg per liter of naphthalene acetic acid). Chemical and strand thinning were done in the Hubabok stage (about 4 weeks after pollination) and the Kimri stage (12 to 13 weeks after pollination), respectively. In two consecutive years, the fruits were transferred to the plant physiology laboratory of the Department of Horticultural Sciences, Faculty of Agriculture, Shahid Chamran University of Ahvaz. The qualitative traits such as total soluble solids (%), pH, total acidity (%), taste index, antioxidant activity (%), total phenol (mg.g-1 FW), total soluble tannin (mg.g-1 FW), ascorbic acid (mg.g-1 FW), poly-galacturonase enzymes (U.g-1 FW), methyl pectin esterase (U.g-1 FW), cellulase (U.g-1 FW) and invertase (U.g-1 FW) and the percentage of reducing (%), non-reducing (%) and total sugars (%) were measured. Results and DiscussionThe results of this experiment showed that in the Tamar Stage, the interaction of hand and chemical thinning improved the qualitative characteristics of the fruit and on the characteristics of soluble total tannin, polygalactronase activity, pectin-methylesterase and reducing and total sugars, and the effect of hand thinning on total and percentage phenol and Non-reducing sugar and chemical thinning had a significant effect on ascorbic acid and cellulase enzyme. The results showed that there was upward trend in amount of total soluble solids, pH, total acidity, taste index, poly-galactronase, pectin-methyl-esterase, cellulase and invertase enzymes and the reducing and total sugars from the Kimri to Tamar stage. Also, there was downward trend in amount of total phenol, total soluble tannin content, ascorbic acid, and non-reducing sugar percentage from the Kimri stage to the Tamar. ConclusionsThe Khadrawi date variety has short strands, which results in a significant density of fruits on the strands of a cluster, which leads to large changes between fruits in most of the biochemical properties and has a negative effect on marketability. Fruit thinning is one of the most important agronomic practices in groves, as it enhances the quality characteristics of the fruit. Although hand thinning is more expensive, time-consuming, and relatively more difficult than chemical thinning, our findings showed that the quality of date fruit from the Khadrawi cultivar improved with the removal of 25% of the total number of strands and with chemical thinning using 100 mg/liter of naphthalene acetic acid. These treatments are recommended for palm growers.